2011
DOI: 10.1071/bt11170
|View full text |Cite
|
Sign up to set email alerts
|

Detecting karrikinolide responses in seeds of the Poaceae

Abstract: The smoke-derived chemical karrikinolide commonly triggers seeds in the Brassicaceae, Solanaceae and Asteraceae families to germinate, yet species in the Poaceae – another major understorey and weed family – have responded to the chemical with mixed results. This study aimed to understand why some grass species respond to karrikinolide while others do not. Using a field-based seed-burial trial, dose-response experiment, and stratification experiment, we investigated whether karrikinolide could alleviate dorman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…However, responses to smoke solutions are complex and may also depend on other factors, such as temperature and light (Long et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…However, responses to smoke solutions are complex and may also depend on other factors, such as temperature and light (Long et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The preincubation experiments also indicated higher sensitivity of caryopses to KAR 1 than to GA 3 . Previously, it was also demonstrated that KAR 1 (Daws et al 2007;Kępczyński et al 2010;Kępczyński and Van Staden 2012;Long et al 2011;Stevens et al 2007) and GA 3 (Adkins et al 1986; Daws et al 2007; Kępczyński et al 2006;Stevens et al 2007) stimulated germination of dormant and partially dormant A. fatua caryopses. Dry storage (after-ripening), is commonly used to remove seed dormancy in many plant species, including A. fatua caryopses.…”
Section: Discussionmentioning
confidence: 99%
“…moisture, temperature, light) and chemical (see examples below) environment. The roles of moisture and temperature in alleviating physiological dormancy are particularly well studied, and the following naturally occurring processes may contribute to dormancy loss: ( i ) dry after‐ripening (sustained dry conditions) (Foley, ; Chauhan & Johnson, ; Iglesias‐Fernández, del Carmen Rodríguez‐Gacio & Matilla, ); ( ii ) cold and warm stratification (wet conditions below or above 10°C, respectively) (Schütz & Rave, ; Turner et al , ; Footitt et al , , ); ( iii ) wet‐dry cycling (alternating periods of wetting and drying) (Gallagher, Steadman & Crawford, ; Batlla & Benech‐Arnold, ; Hoyle et al , 2008 a ; Long et al , 2011 b ); and ( iv ) alternating temperatures (Batlla & Benech‐Arnold, ; Footitt et al , ; Long et al , 2011 c ).…”
Section: Seed Characteristics That Influence Persistencementioning
confidence: 99%